FACTORS AFFECTING THE PURCHASE INTENTION OF IPHONE PRODUCTS AMONG GEN Z - Angelica, Katty; Utama, Louis (Graduate Program of Universitas Tarumanagara, 2025)
This study investigates the factors influencing purchase intentions for iPhone products among Generation Z, specifically focusing on students at Tarumanagara University. The research examines the impact of brand trust, perceived value, and brand preference on purchase intention, using the Theory of Planned Behavior (TPB) as a theoretical framework. A quantitative research design with descriptive data analysis was employed, and 171 respondents participated through purposive sampling. Data were collected via an online questionnaire and analyzed with SmartPLS, evaluating the validity, reliability, and structural relationships between variables. Results indicate that brand trust and perceived value significantly enhance brand preference and purchase intention. The findings highlight the importance of fostering brand trust and delivering perceived value to increase Gen Z's interest in purchasing iPhone products. This study provides valuable insights for marketers on strengthening brand loyalty and preference to drive sales within this demographic.